Seed-Mediated Growth of Gold Nanorods Using Silver Seeds: Effect of Silver Seeds Concentration and Growth Time - Nafisah, Suratun; Morsin, Marlia; Jumadi, Nur Anida; Nayan, Nafarizal; Shah, Nur Zehan Anâ€™nisa Md; Razali, Nur Liyana; Soon, Chin Fhong (International Journal of Engineering and Technology, 2018)
Seed-mediated growth method (SMGM) in preparation of gold nanoparticles becomes one of the most popular methods due to the simplicity of the experimental procedures and flexibility in structural modifications. In this paper, we report a new method for synthesizing gold nanoparticles using silver seeds. The effect of seed concentration and growth time are investigated in this work. By increasing the silver seed concentration, it is found that the color of the colloidal gold nanorods obtained are changed from light pink to reddish purple, the surface plasmon resonance band is shifted to the blue region whereas absorption spectra becomes narrower. The additional peak is also spotted when increasing silver seed concentration to 5 Âµl. Meanwhile, increasing the growth time from 5 to 240 minutes tends to increase the color concentration of the solution. Besides that, the absorbance of colloidal gold nanorods is also increased with an increase in the growth time whereas optimum growth time is found to be 45 minutes. FESEM characterization shows that gold nanoparticles shapes are dominated by nanorods with average length, width, and aspect ratio are 129.8 nm, 42.9 nm, and 3.4, respectively. The energy-dispersive x-ray spectroscopy (EDX) shows the chemical composition of the synthesized sample is Gold (Au) with weight % and atomic % are 32.23 and 5.98, respectively. Besides that, signals from Carbon (C), Oxygen (O), and Indium (In) atoms were also recorded from EDS spectra. The present approach thus provides new method for synthesis gold nanoparticles with additional plasmon resonance peak thus it has very potential for application in plasmonic sensing.